Pengenalan Chatgpt Dalam Penyusunan Instrumen Tes Berbasis Taksonomi Bloom Di Madrasah Aliyah Negeri 1 Boalemo - Asrul, Asrul; Pratama, M. Iqbal Liayong (-, 2024)
The advancement of artificial intelligence (AI) technology has opened up new opportunities in education, particularly through the use of ChatGPT as a tool for constructing test instruments based on Bloom's Taxonomy. This study aims to introduce and train teachers at MAN Negeri 1 Boalemo in utilizing ChatGPT to develop structured and effective exam questions aligned with the cognitive levels of Bloom's Taxonomy. The training methods included lectures, demonstrations, discussions, and hands-on practice, aimed at enhancing teachers' skills in using AI to support learning activities. The results of the training indicated significant improvements in the teachers' ability to create questions based on Bloom's Taxonomy. The average evaluation score of the participants was 93.07%, with most participants scoring between 4.50 and 5.00. Of the 16 participants, 6 teachers achieved a perfect score of 5.00, demonstrating a strong understanding of ChatGPT's application in test construction. The training proved effective in equipping teachers with new knowledge and skills, motivating them to integrate technology into the learning process. Overall, the training successfully enhanced teachers' creativity and efficiency in designing exam questions, and further training on related topics is recommended.